Study on the Design and Tactile Percention of New Fully Actuated Bionic Hand - Xuewen Ping (Jixie chuandong)
Aiming at the problems of poor fine operation performance and tactile perception of underactuated bionic hand，a new bidirectional fully actuated bionic hand is designed by means of electromagnetic reversal and belt driving. The 15 finger joints of the five-fingered bionic hand are independently driven by a single motor，and an experimental prototype is manufactured. By adopting the single current and multi-angle sensor used in combination，not only accurate control of finger joint angle is realized，at the same time，through the study of the data acquisition of angle sensor and drive current and matching processing，the current amplitude change and the joint force，current change rate and the mathematical model of hardness are established，which enrich the bionic hand tactile perception ability. A platform is built to test the grasping ability of the bionic hand，which shows the bionic hand presents good grasping characteristics when the current and angle sensor are used together，and the bidirectional independent driving mode improves the grasping efficiency of the bionic hand.